Efficacy of probiotics in dermatitis herpetiformis management: an umbrella review - Alghuyaythat, Waleed Khalid Z; Alfaifi, Fawziah Salman; Alshalhoob, Hind Bader S.; Abanumay, Rana Khalid A.; Asiree, Rayan Hussain A.; Alnumayr, Haya Sulaiman; Alanazi, Anwar Ghudair T.; Alluli, Maryam Mohammed (Frontiers in Physiology, 2025)
BackgroundThe available evidence on probiotics in Dermatitis Herpetiformis (DH) remains severely limited. Given the shared pathophysiology of DH and Coeliac disease (CD), we aimed to provide the hypothesis to synthesize the narrative reviews carried out so far on the use of probiotics in the treatment of DH, its impact on gut microbiota dysbiosis, and the gut-skin axis.MethodsRelevant narrative reviews were searched for in electronic databases such as PubMed, Scopus, Cochrane Library, Embase, and Google Scholar.ResultsAll 7 included reviews commented on gut microbiota dysbiosis as a common feature in patients with CD and DH. Immune modulation, attenuation of intestinal permeability, and anti-inflammatory effects were some of the postulated effects of probiotics. Probiotics could modulate the gut-skin axis and may prove therapeutic for DH; however, most of the evidence was indirect, drawn from models of CD or theoretically derived.ConclusionWhile probiotics showed promise for managing gut dysbiosis and immune regulation in DH, the existing evidence remains speculative. Our results suggest that probiotics could be a useful adjunct to gluten-free dieting in DH treatment, but future studies are needed to support this finding.